2017
DOI: 10.1002/gps.4773
|View full text |Cite
|
Sign up to set email alerts
|

Increased N200 and P300 latencies in cognitively impaired elderly carrying ApoE ε‐4 allele

Abstract: Latencies of N200 and P300 increased in cognitively impaired patients with the presence of ApoE ε-4 allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…The majority of the 25 studies that analyzed P300 amplitude reported smaller amplitude in AD compared to HC groups [i.e., 60%; 3,4,13,42- 43,60,63,71,84,89,114,118,142,145,152], including one reporting a trend that did not reach statistical significance[42]. The remaining ten studies reported no significant difference between groups [i.e., 40%;31,47,69,[72][73]92,105,110,126,139]. These latter AD studies were notable for small sample sizes (e.g., eight per cell), age differences between groups, high AD group MMSE scores (e.g., 27/30), and/or simple tasks (i.e., 67% oddball paradigms), which may have limited power to detect group differences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the 25 studies that analyzed P300 amplitude reported smaller amplitude in AD compared to HC groups [i.e., 60%; 3,4,13,42- 43,60,63,71,84,89,114,118,142,145,152], including one reporting a trend that did not reach statistical significance[42]. The remaining ten studies reported no significant difference between groups [i.e., 40%;31,47,69,[72][73]92,105,110,126,139]. These latter AD studies were notable for small sample sizes (e.g., eight per cell), age differences between groups, high AD group MMSE scores (e.g., 27/30), and/or simple tasks (i.e., 67% oddball paradigms), which may have limited power to detect group differences.…”
mentioning
confidence: 99%
“…The majority reported delayed latency in AD compared to HC groups [i.e., 66%; 3,43,52,60,63,71,76,88,92,96- 97,105,110-111,118,135,139,142,145,152], two of which reported non-significant trends[52,145]. No significant differences between groups were detected in eight studies [i.e., 27%; 4,31,47,69,75,84,114,126]. Two studies in fact reported shorter P300 latency in AD compared to HC groups [i.e., 7%; 13,72], although interpreting this in context of other studies is difficult because one also reported high P300 variability in the AD group[13], and the other used an Three of five APOE studies reported delayed P300 latencies in the ɛ4+ group when using an olfactory identification task [i.e., 60% of total studies;93,95,147].…”
mentioning
confidence: 99%
“…All 14 articles included were cross-sectional investigations. 14-27 Studies were conducted in 5 different countries: the United States (n = 7 studies), 16-18,20,21,23,27 Norway (n = 3 studies), 19,24,25 China (n = 2 studies), 15,26 Brazil (n = 1 study), 14 and Taiwan (n = 1 study). 22…”
Section: Resultsmentioning
confidence: 99%
“…The P300 is very clearly correlated with cerebral aging and provides a distinction between neurodegenerative diseases such as Alzheimer's disease and thymic disorders [20][21][22].…”
Section: Cardiovascular Evaluation and Other Measuresmentioning
confidence: 99%